Epidemiological Analysis of Multidrug-Resistant Acinetobacter baumannii Isolates in a Tertiary Hospital Over a 12-Year Period in China - Jiang, Meijie; Chen, Xia; Liu, Shuang; Zhang, Zhijun; Li, Ning; Dong, Chao; Zhang, Ling; Wu, Haiyan; Zhao, Shuping (Frontiers in Public Health, 2021)
Acinetobacter (A.) baumannii is an important nosocomial pathogen, multidrug-resistant (MDR) A. baumannii has become a major threat to public health worldwide due to the ability to easily acquire resistant genes. In order to analyze the epidemiology characteristics and the genetic evolution of A. baumannii isolates obtained from a Chinese tertiary hospital in the past 12 years (2008 - 2019), 295 isolates of non-repetitive A. baumannii were recovered from patients and wards environments. The antimicrobial susceptibility testing, the resistance genes were analyzed. The genetic relatedness of 295 isolates was identified by multilocus sequence typing (MLST) and eBURST analysis. It was found that the antibiotics resistance and carbapenemase resistance genes of all 295 MDR A. baumannii in the hospital have not changed significantly over the past 12 years, all of them were resistant to multiple antibiotics except the polymyxin E and tigecycline. The results of drug-resistant genes showed that the detection rates of carbapenemases resistance genes blaOXA-23, blaTEM-1, and blaOXA-66 were 97.6%, 75.3%, and 71.9%, respectively, which were detected almost every year from 2008 to 2019. Additionally, 16s rRNA methylation enzymes gene armA, aminoglycoside resistant gene ant(3″)-Ⅰ and class I integrase gene could also have high positive rate. By MLST, these isolates were assigned to 12 sequence types (STs), including ST369, ST208, ST195, ST191, ST368, ST530, ST469, ST451, ST229, ST381, ST543, and ST1176. eBURST analysis showed that 9 STs with ST208 as the founder genotype belonged to group 1 except for ST229 ST530 and ST1176. Therefore, most MDR A. baumannii isolates had relatively close genetic relationship. Notably, the predominant ST208 and ST369 at the early stage changed to ST451 in 2019, indicating that the complex and diverse genetic background of the prevalence A. baumannii isolates in the hospital. Overall, the further epidemiological surveillance and genetic evolution analysis of A. baumannii is required, which provided new strategies for the prevention and control of A. baumannii infections.